Thymoma‐associated multi‐organ autoimmunity: A case of graft‐versus‐host disease‐like erythroderma complicated by Good syndrome successfully treated by thymectomy. Issue 7 (3rd March 2017) - Fukushima, Ayano; Ichimura, Yoshiko; Obata, Shoko; Kinoshita‐Ise, Misaki; Fujio, Yumi; Takeno, Mitsuhiro; Konohana, Izumi
Abstract: Thymoma‐associated multi‐organ autoimmunity disease (TAMA) is a rare paraneoplastic disorder, clinicopathologically similar to graft‐versus‐host disease (GVHD). Many reported cases follow a difficult course; half of them die from serious infectious diseases subsequent to immunosuppression induced by chemotherapy for unresectable thymoma, or intensive therapies including systemic steroids for complicating autoimmune diseases and GVHD‐like symptoms. We report a patient whose skin symptoms were improved subsequently to total thymectomy. The patient also presented with hypogammaglobulinemia, which led to the diagnosis of complicated Good syndrome. Taking account of her immunodeficient condition, antibiotics and i.v. immunoglobulin were administrated promptly on onset of bacterial pneumonia, which was successfully treated. According to a review of the published work, treatments with systemic steroids for skin symptoms have limited effects and may contribute to serious infection. Our case indicates that successful treatment of thymoma itself may lead to the amelioration of the disease. The management priority should be given to the treatment of thymoma and the control of subsequent immune abnormality other than GVHD‐like erythroderma.